Study on PLA and PA thermoplastic polymers reinforced with carbon additives by 3D printing process. (2021) - N, Arunkumar; N, Sathishkumar; S.S, Sanmugapriya; R, Selvam
Abstract: In this study a modest attempt has been made to analyze the impact of anisotropic nature of 3D printing process over carbon fiber reinforced PLA and PA parts. The parts were fabricated by using NEXG X3045 Fused Deposition Modeling printer with two infill densities say 50% and 99%. The honeycomb shape infill pattern was used with a fixed raster angle of 45 degree orientation. The parts were fabricated as per ASTM standards and subjected to tensile, impact and bending tests under varying load range. The PLA + CF sample with 99% infill density exhibited a maximum value of 25.6Mpa tensile strength. The flexural strength (30.12 KJ/m 2 ) and bending strength (49.41 Mpa) of the PA + CF sample with 99% infill density was found better than other samples. The scanning electron microscope images shows the infill percentage as a major input parameter which influencing the outcomes of this study significantly.